Presidential Advisory Boards in Chile: Between Expertise and the Plurality of Social Actors [Comisiones Asesoras Presidenciales en Chile: Entre la Expertise y la Pluralidad de Actores Sociales] - Vasquez-Fajardo, J (Centre for Latin American Research and Documentation/Centro de Estudios y Documentación Latinoamericanos (CEDLA), 2018)
This article studies the social background of one of the most used public deliberation mechanism by the executive branch: the presidential advisory commissions. A thorough description of its members is offered, and, using a Social Network Analysis (SNA), it explores and compares the use of this mechanism between ideologically opposed governments. Similar tendencies in both administrations are noted, and the important predominance that the Chilean intellectual community has in these pre-legislative instances is also distinguished. Although other actors of the political and social fields are called to participate in these spaces, the pragmatic technocrats, agents with important academic credentials and non-political outsiders are the ones who head civil expertise at the presidential level. © Carla Cisternas & Javiera Vásquez.
Keywords: Chile; Expertise; Intellectual elites; Political elites; Technocracy